Salmonellosis outbreak associated with the consumption of food at a wedding in an urban restaurant in Kazakhstan: a retrospective cohort study - Saya Gazezova; Dilyara Nabirova; Michelle Waltenburg; Maral Rakhimzhanova; Manar Smagul; Lena Kasabekova; Roberta Horth (BMC Infectious Diseases)
Abstract Background From June 13–16, 2022, a regional epidemiological department in Kazakhstan reported an increase in acute gastroenteritis cases among people who consumed food from a wedding at a restaurant. An investigation was initiated to determine factors associated with acute intestinal infection and prevent further illness. Methods The investigation team conducted a retrospective cohort study among people who consumed event food. Participants were classified as a case if they were acutely ill with diarrhea, vomiting, fever, vomiting, or weakness from June 13–18. We interviewed people to collect information on demographics, symptoms, and food exposures at the event. We calculated food-specific attack rates and estimated adjusted relative risks (aRR) using multivariable Poisson regression, which was adjusted for sex, age, and foods consumed. Patient stool and gastric lavage samples, leftover food, and restaurant environmental samples were collected for bacterial culture and chemical analysis. Results Of the 138 participants, 66 became ill; the attack rate was 48%. The most reported symptoms were diarrhea (92%), abdominal pain (91%), and fever (89%). Symptom onset occurred between 6 h and 4 days after the event (median = 1 day). Overall, 50 (76%) cases were hospitalized; no deaths were reported. In bivariable analysis, a greater proportion of cases than non-cases ate honey cake (89% vs. 13%, p < 0.01), and 45% of cases ate leftovers compared with 11% of non-cases (p < 0.01). In multivariable analysis, honey cake was the only risk factor associated with illness (aRR = 7.8, 95% confidence interval = 3.5–20.1, p < 0.01). Honey cakes, which use raw eggs in cream layers, had been stored at room temperature for three days before the event. Salmonella enterica serovar Enteriditis (S. Enteritidis) was isolated from all patient stool samples (49/49, 100%) and honey cake samples (2/2, 100%). Staphylococcus aureus was detected in 92% (35/38) of patient gastric lavage samples. Conclusion S. Enteritidis was this outbreak’s most probable etiological agent based on clinical manifestations and isolation from participant and honey cake samples. The improper storage of cakes containing raw eggs was a key contributing factor. Leftover event food was discarded, and the restaurant was closed for disinfection. Future outbreaks could be prevented by increased food safety awareness.